The Analisis Dampak Struktur Modal Terhadap Profit Perusahaan Periode 2016-2023 - Riri Prihatin; Maria Magdalena Manalu; Graciana Martha Siri (Journal of Trends Economics and Accounting Research, 2024)
This study aims to examine the impact of capital structure on the profitability of PT Jamkrida Jakarta from 2016 to 2023. A quantitative method with a descriptive approach was employed, using secondary data sourced from the company’s financial statements. The population in this research includes all financial reports of PT Jamkrida Jakarta, while samples were selected using the saturated sampling technique. Data analysis was conducted through simple linear regression with the help of SPSS software version 25.0 for Windows. The findings indicate that capital structure has a significant and positive effect on profitability, as demonstrated by a t-value higher than the t-table value (2.645 > 2.306) and a significance level of 0.034, which is below 0.050. Thus, H0 is rejected, and Ha is accepted, confirming a positive relationship between capital structure and profitability. The R Square (R²) value of 0.538 reveals that 53.8% of profitability variability is accounted for by changes in capital structure. These findings provide strategic insights for PT Jamkrida Jakarta in optimizing its capital structure to enhance profitability amidst dynamic economic conditions.